Targeting the pregnane X receptor using microbial metabolite mimicry - Zdeněk Dvořák; Felix Kopp; Cait M Costello; Jazmin S Kemp; Hao Li; Aneta Vrzalová; Martina Štěpánková; Iveta Bartoňková; Eva Jiskrová; Karolína Poulíková; Barbora Vyhlídalová; Lars U Nordstroem; et al. (EMBO Molecular Medicine)
Abstract The human PXR (pregnane X receptor), a master regulator of drug metabolism, has essential roles in intestinal homeostasis and abrogating inflammation. Existing PXR ligands have substantial off‐target toxicity. Based on prior work that established microbial (indole) metabolites as PXR ligands, we proposed microbial metabolite mimicry as a novel strategy for drug discovery that allows exploiting previously unexplored parts of chemical space. Here, we report functionalized indole derivatives as first‐in‐class non‐cytotoxic PXR agonists as a proof of concept for microbial metabolite mimicry. The lead compound, FKK6 (Felix Kopp Kortagere 6), binds directly to PXR protein in solution, induces PXR‐specific target gene expression in cells, human organoids, and mice. FKK6 significantly represses pro‐inflammatory cytokine production cells and abrogates inflammation in mice expressing the human PXR gene. The development of FKK6 demonstrates for the first time that microbial metabolite mimicry is a viable strategy for drug discovery and opens the door to underexploited regions of chemical space.